Bmi, Age, Mate Value, and Intrasexual Competition in Chilean Women - Fernandez-Tapia, A (Springer New York LLC, 2014)
Attractiveness is the most important component of women intrasexual competition and it certainly has an impact in female’s perceived mate value (i.e., the value of an individual to the opposite sex as a potential mate). In the realm of intrasexual competition women are eager to emphasize their attractiveness and compete with rivals displaying these cues. Accordingly, age is an important feature of women’s appeal to the opposite sex; youth is highly valued by men, and is perceived by women as an important component of their attractiveness. Another trait that is a reliable cue of health and fertility is Body Mass Index (BMI). A large body of literature has associated BMI to female attractiveness. However, more information is necessary about the associations of BMI and age with mate value, and female intrasexual competition. In the present research we report two studies that examined the associations of BMI and age with estimates of self-perceived mate value and intrasexual competition in Chilean women (18–39 years). More specifically, we hypothesized inverse relationships of BMI and age with mate value (N = 234), and intrasexual competition (N = 308). We found partial support to our propositions. The results revealed inverse associations between BMI, mate value and mating success, but BMI with intrasexual competition were not related. In contrast, age had a strong and negative effect on intrasexual competition. We discuss our results within the framework of Evolutionary Psychology and consider the central role of attractiveness (estimated from BMI and age) in the mating strategies of women. © 2014, Springer Science+Business Media New York.